THE EFFECT OF COGNITIVE STRATEGIES ON THE STUDENTS’ LISTENING COMPREHENSION AT STMIK PRABUMULIH - Hepnyi Samosir (ELTE Journal (English Languange Teaching and Education), 2017)
This study is an experimental design that aims to find out if there is any significant difference in the students’ listening comprehension taught by using cognitive strategies. The study was conducted at STMIK Prabumulih. The population taken was the fourth semester students. The samples were taken by random sampling technique. Pre-test and post-test were carried out with participant students from the two classes, experimental and control class. The experiment class showed an average of 40 in the pre-listening test. On the other hand, the control class showed an average of 35 when doing the pre-listening test. After being treated with cognitive strategies, then the post-listening test was carried out. The experiment class showed an average of 70, whereas the control class got 50.83. The mean gain for control class was 16.50, and for the experimental class were 27.50. Both classes differ in gains in which the mean gain for experiment class was higher than the other one. It was found that t-observed was greater than the value of t-table (4.63 > 1.671) and thus null hypothesis was successfully rejected. It could be interpreted that cognitive strategies affected the students’ listening comprehension. The result of cohen’s d is 1.19, and categorized as large. With the Cohen’s d of 1.19, 97.1 % of the treatment classes were above the mean of the control one. The finding of the study is expected to be reference or source of information in designing teaching listening syllabus. Keywords: Effect, Cognitive Strategies, Bottom-up, Top-down